Visual References in the Description of Print Advertisements. A Four-Country Cross-Cultural Analysis. Issue 2 (7th March 2022) - Gliniecka, Martyna
Abstract: This paper investigates cross-cultural differences in the usage, themes, and factors of visual-related references in describing print advertisements. American, Russian, Japanese, and Polish respondents participated in an open-ended survey about three translated ads adapted into the existing visual. Respondents used less visual than non-visual descriptions, and their frequency differed by the ad. Similarities and differences were influenced by the specific advertisement, not by respondents' country. Advertisements require individual assessment for visual adaptation strategy. This pilot study introduces the concept of visual and non-visual descriptions of advertising, visual references themes and variable of advertising case to assess differences between countries.